Effect of three different forms of handling on the variation of aggression-associated parameters in individually and group-housed male C57BL/6NCrl mice - Mertens, Sinja; Vogt, Miriam A.; Gass, Peter; Chourbaji, Sabine (PLOS ONE, 2019)
Mice are social animals hence group-housing of mice is preferred over individual housing. However, aggression in group-housed male mice under laboratory housing conditions is a well-known problem leading to serious health issues, including injury or death. Therefore, group-housed mice are frequently separated for welfare reasons. In this study, we investigated the effect of 3 different handling methods (tail, forceps, tube) in 2 different housing conditions (single vs. group) on the variance of aggression-associated parameters in male C57BL/6NCrl mice over 8 weeks. Blood glucose concentration, body weight, body temperature, plus number and severity of bite wounds and barbering intensity in group-housed mice were recorded. An assessment of nest complexity was also performed weekly. Feces were collected in week 3 and 7 for analysis of corticosterone metabolites. We also monitored the level of aggression by recording the behavior of group-housed animals after weekly cage cleaning. An open field test followed by a social novel object test, a light/dark box test, a hotplate and a resident-intruder test were performed at the end of the 8-week handling period. Post-mortem, we assessed organ weights. We found that forceps-handled mice, independent of the housing condition, had significantly higher levels of stress-induced-hyperthermia and enhanced aggression after cage cleaning, and they performed worse in the nest complexity test. In addition, handling male mice by the tail seems to be most effective to reduce aggressiveness after transferring animals into new cages, thereby representing an appropriate refinement.